Pengaruh Biaya Acrual dan Discretionary terhadap Nilai Perusahaan Manufaktur di Bursa Efek Indonesia dengan Good Corporate Governance sebagai Variabel Moderating - Mangasi Sinurat; Rico Nur Ilham (The Indonesia Capital Market Institute, 2020)
Purpose - This study discusses the effect of discretionary and discretionary accruals on firm values ​​with good corporate governance as a moderating variable in manufacturing sector companies in Indonesia. Methods - The data used are secondary data containing annual reports and financial statements of manufacturing sector companies that discuss the Indonesian Stock Exchange. The sample used in this study was 47 companies with an observation period of 5 (five) years from 2014-2018. The analysis used in this study is multiple linear regression analysis. Finding - Partial discretionary positively influence on model 1 and negatively on model 2 but not significantly to firm value, while discretionary costs have a positive and significant effect on firm value. No GCG practices can moderate the relationship of discretionary accruals to firm value, while independent commissioners, audit quality, institutional ownership, and managerial ownership can moderate the relationship of discretionary prices with firm value. The effect of discretionary and discretionary accrual costs simultaneously a significant effect on firm value. Discretionary and discretionary accrual costs with good corporate governance as a moderating variable.